2017
DOI: 10.1016/j.neurobiolaging.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Central amygdala activation of extracellular signal-regulated kinase 1 and age-dependent changes in inflammatory pain sensitivity in mice

Abstract: Aging populations are more sensitive to noxious stimuli as a result of altered somatosensory systems. In these experiments, we examined pain-like behaviors in young, middle-aged, and old mice during peripheral inflammation to determine if the same sensitivity exists in pre-clinical animal models. Immediately following injury, middle-aged and old mice exhibited more spontaneous pain-like behaviors than young mice, matching pain prevalence in clinical populations. Middle-aged and old mice also developed persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…These results are in agreement with the evidence that aged animals develop heightened hypersensitivity in several experimental pain models (Crisp et al, 2003;Bishay et al, 2013) and that formalin test behavioral pattern is influenced by age (Gagliese and Melzack, 1999). Also under different experimental conditions (10 ml of 4% formalin solution (Kolber et al, 2010)), C57BL/6 mice display enhanced nociceptive behavior and increased variability among different ages in the second phase and mechanical allodynia (Sadler et al, 2017). Aged C57BL/6J mice present a mitochondrial impairment (Kadoguchi et al, 2020) and a decrease in oxidative phosphorylation as well as alteration in apoptosis regulation (see (Azzu and Valencak, 2017)).…”
Section: Discussionsupporting
confidence: 90%
“…These results are in agreement with the evidence that aged animals develop heightened hypersensitivity in several experimental pain models (Crisp et al, 2003;Bishay et al, 2013) and that formalin test behavioral pattern is influenced by age (Gagliese and Melzack, 1999). Also under different experimental conditions (10 ml of 4% formalin solution (Kolber et al, 2010)), C57BL/6 mice display enhanced nociceptive behavior and increased variability among different ages in the second phase and mechanical allodynia (Sadler et al, 2017). Aged C57BL/6J mice present a mitochondrial impairment (Kadoguchi et al, 2020) and a decrease in oxidative phosphorylation as well as alteration in apoptosis regulation (see (Azzu and Valencak, 2017)).…”
Section: Discussionsupporting
confidence: 90%
“…However, other experiments comparing von Frey thresholds across similarly aged mice have reported no differences 16 or reduced sensitivity with increasing age. 24 Most experiments have used inbred C57BL/6 mice, rather than the outbred CD-1 mice used here. In the same manner as sex differences in pain and pain inhibition have been shown to interact thoroughly with genetic background, 10 , 20 aging effects almost certainly do as well.…”
Section: Discussionmentioning
confidence: 99%
“…We found that KOR antagonism in the right CeA, but not the left CeA or RVM, prevented the loss of DNIC measured in either hindpaw in morphine primed animals. A lateralized role of the amygdala has been shown in inflammatory [13,33,63,75] and neuropathic pain [28] models and mGluR5 activation in the right, but not left, CeA is sufficient to produce peripheral hypersensitivity in the absence of injury [39]. Recently, we demonstrated that microinjection of a KOR agonist into the right, but not left, CeA produced allodynia in both hindpaws following priming with sumatriptan to model medication overuse headache [91].…”
Section: Discussionmentioning
confidence: 99%